The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1121/1.5049895
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a model of temporal weights in loudness judgments

Abstract: The onset of a sound receives a higher weight than later portions in time when its loudness is assessed, an effect commonly referred to as primacy effect. It is investigated if this effect can be predicted on the basis of an exponentially decaying function where the weight assigned to a temporal portion of a sound is the integral of this function over the segment duration. To test this model, temporal loudness weights were measured for sounds with different segment durations and total durations. The model succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In the present data, the estimated τ was about 240 ms for the conditions in background noise, whereas for the conditions in quiet, τ varied between 217 and 355 ms. Previous studies showed a dynamic range D r of about 4.70 for comparably long sound durations [10,11]. In the current study, a similar dynamic range ( D r = 5.05) was only found for condition Quiet SLquiet7.5 , whereas all other conditions showed higher dynamic ranges with D r between 10 and 27.48.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…In the present data, the estimated τ was about 240 ms for the conditions in background noise, whereas for the conditions in quiet, τ varied between 217 and 355 ms. Previous studies showed a dynamic range D r of about 4.70 for comparably long sound durations [10,11]. In the current study, a similar dynamic range ( D r = 5.05) was only found for condition Quiet SLquiet7.5 , whereas all other conditions showed higher dynamic ranges with D r between 10 and 27.48.…”
Section: Resultssupporting
confidence: 79%
“…To quantify the magnitude and time course of the primacy effect, exponential decay functions were fitted to the mean weights at each of five conditions, as proposed in our previous work [10,11]. The weight assigned at the time t was assumed to be where t = 0 corresponds to the sound onset, c is the asymptotic weight at t → ∞ , D r is the weight at sound onset ( t = 0) relative to the asymptotic weight w ( ∞ ) = c (i.e., D r is the "dynamic range" of the weights), and the time constant τ quantifies the time needed for the weight to decay to a value of 1/ e of the weight range between w (0) and the asymptotic weight c .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations